Expanding guinea yam (Dioscorea spp.) production in Uganda: results of a short survey in Luweero district - Coyne, Danny L.; Kajumba, C.; Asiedu, Robert (2005)
Over recent years, pest and disease epidemics have affected the reliability of the main food crops in Uganda. Attempts to improve crop diversity therefore, and reduce reliance on the key staple crops, have included the promotion of yam (Dioscorea spp.) through the introduction of improved cultivars (cvs), breeder's lines and seed populations of Dioscorea rotundata by the lnternational Institute of Tropical Agriculture (llTA) in coordination with the National Agricultural Research Organisation of Uganda. Selections from the introduced germplasm, made on-station in collaboration with farmers, were multiplied and given to interested farmers in selected districts in the country for further multiplication and testing in comparison with local yam cvs. The current study assessed the extent of the uptake of the introduced germplasm in one district (Luweero), their acceptance by farmers and farmer perception of future yam production. The selections from the introduced germplasm were well accepted and all farmers who received them have continued to produce them. Farmers who did not receive them have since adopted them. The previously most preferred cv, Kyetutumula, a Dioscorea cayenensis, remains the most preferred, essentially due to its taste. The introduced germplasm were in general well liked, depending on the clone, but farmers are less willing to increase their investment in expansion of them due to variability between clones, including taste. A main reason for not expanding production of either the introductions or other cvs, however, is the lack of (healthy) planting material and information regarding the introductions. Farmers are willing and intend to expand production of yam in Luweero. There is need however, for increased supply of healthy planting material and training in yam production techniques. Farmers and extension agents are already requesting material and aid, in order to counteract losses from the current epidemic of banana bacterial wilt disease.